Efficacy and safety of the ayurvedic formulation ‘Trikatu’ as an add-on to standard care in dyslipidemia: Study protocol for a randomized, double-blind, placebo-controlled trial evaluating lipid parameters, and gut microbiota - Shruti Khanduri; Sophia Jameela; Suchanda Sahu; Sujata Devi; Bhogavalli Chandra Sekhara Rao; Kshirod Ratha; Richa Singhal; Latika Kaushik; Narayanam Srikanth; Rabinarayan Acharya (PLoS ONE, 2026)
Background Dyslipidemia is a leading modifiable risk factor for cardiovascular disease (CVD), with early and sustained LDL-C reduction offering significant preventive benefits. However, in low- and middle-income countries, long-term adherence to statin therapy remains alarmingly low, highlighting the need for culturally acceptable and safer adjunctive options. Trikatu , a classical Ayurvedic formulation traditionally known to enhance metabolism, may offer supportive benefits in lipid regulation. This study protocol was developed to assess the efficacy and safety of Trikatu as an add-on to standard statin therapy on lipid parameters and assess changes in gut microbiota in response to the intervention and identify microbial correlates associated with favorable lipid outcomes. Methods This randomized, double-blind, placebo-controlled clinical trial is being conducted at AIIMS Bhubaneswar, a tertiary care center. Total 170 participants (aged 25–60 years) with moderate to high Atherosclerotic cardiovascular disease (ASCVD) risk. Dyslipidemia, as defined by the 2019 ACC/AHA Guidelines and indicated for statin therapy, will be randomized in a 1:1 ratio to receive either Trikatu (1000 mg) or matching placebo, administered orally twice daily after food for 12 weeks along with standard statin therapy (dose/intensity as per guidelines). Primary outcome includes change in fasting serum LDL-C from baseline to 12 weeks. Secondary outcomes include changes in total cholesterol, HDL-C, triglycerides, glycemic markers (fasting glucose, HbA1c, insulin, HOMA-IR), inflammatory and metabolic markers (hs-CRP, TNF-α, IL-6, adiponectin, ghrelin, ApoA1, ApoB), resting blood pressure, and gut microbiota. The proportion of participants achieving normal cholesterol levels (<200 mg/dL) will also be assessed. Drug compliance and any adverse events will also be recorded. Discussion In individuals with moderate to high ASCVD risk, achieving and sustaining optimal lipid control remains a cornerstone of cardiovascular prevention. However, poor long-term adherence to statin therapy, especially in low-resource settings, limits real-world impact. By assessing Trikatu, effects on lipid profiles, glycemic and inflammatory markers, and gut microbiota, the study aims to explore its potential to augment cardiovascular risk reduction in a holistic and culturally acceptable manner. If proven effective and safe, Trikatu could serve as a valuable complementary strategy in dyslipidemia management. Clinical Trial Registration Clinical Trial Registry of India (CTRI/2023/04/051942) Registered on 25/04/2023.